Retinal Neuropathy in IGT Stage of OLETF Rats: Another Characteristic Change of Diabetic Retinopathy - Zhenhong Guo; Xiaoyue Sun; Juhong Yang; Jinlan Xie; Feifei Zhong; Xinran Li; Yi Zhang; Fei Han; Xiaoyun Yang; Shaohua Yang; Wei Zhou; Baocheng Chang (Journal of Diabetes Research)
Aims. We investigated the changes of retinal structure in normal glucose tolerance (NGT), impaired glucose tolerance (IGT), diabetes mellitus (DM), and diabetic kidney disease (DKD) stages in Otsuka Long-Evans Tokushima Fatty (OLETF) rats. Methods. We assigned OLETF rats to four groups based on their OGTT results and 24 h urinary microalbumin (24 h UMA) levels: NGT, IGT, DM, and DKD groups. We observed the structural and the corresponding pathological changes and quantified the expression of HIF-1α, iNOS, NF-κB, VEGF, ICAM-1, and occludin in the retina. Results. Significant damage to the retinal structure, especially in retinal ganglion cells (RGCs), was observed in the IGT stage. The expression of HIF-1α, iNOS, NF-κB, VEGF, and ICAM-1 was significantly upregulated, while that of occludin was downregulated. Conclusion. Significant retinal neuropathy occurs in the IGT stage. Inflammation and hypoxia may damage the blood retina barrier (BRB), leading to diabetic retinopathy.